Beyond international prognostic index: risk stratification in diffuse large B-cell lymphoma - Gao, Hongyu; Gong, Zimu (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
Diffuse large B-cell lymphoma (DLBCL) is the most common subtype of non-Hodgkin lymphoma (NHL). Both the clinical behavior and the underlying biological process are very heterogeneous in DLBCL, suggesting the necessity of utilizing individualized and risk adapted therapy. The international prognostic index (IPI) has been widely used for risk evaluation in DLBCL. Although IPI could successfully differentiate DLBCL patients into four groups with different outcome in the era of conventional chemotherapy, the efficacy of the IPI has declined in the era of rituximab. Newer prognostic systems, including the revised IPI (R-IPI) and the enhanced IPI (NCCN-IPI), have shown superiority over the traditional IPI in predicting outcome in DLBCL patients treated with rituximab based therapy. Risk stratification system based solely on clinical factors is feasible in daily practice, but they can not necessarily reflect the underlying biological process, and it’s very hard to tailor targeted therapy based on solely clinical information. Over the past decade, numerous biomarkers were shown to be prognostic or predictive. However, incorporating biomarkers and clinical factors in one risk stratification system remains challenging.